Concept of Misaqan Ghalidzan in Contemporary Interpretation of Quraish Shihab Thoughts - Syafi'i, Imam; Faiqoh, Ruqoyatul; Fronzoni, Vasco (Faculty of Sharia, IAIN Metro, 2023)
Marriage is a social interaction filled with the essence of worship, extending beyond the union of two individuals including two families. Upon the pronouncement of the marriage agreement, the weight of responsibility would shift from the woman's parents to the husband. Therefore, it is not surprising that Allah calls marriage a heavy and strong bond (Mīṡāqan Ghalīẓan). This study aimed to explore and understand the concept of Mīṡāqan Ghalīẓan (a strong and heavy bond) within the context of marriage. Library, qualitative, and documentation methods were used to interpret al-Mishbah by Quraish Shihab, an Indonesian scholar. The results showed that the scholar used the concept of munāsabah al-ayat by quoting another verse mentioned in Mīṡāqan Ghalīẓan, namely equating strong religious commitment with marriage agreement and the obligation to maintain the bond. Furthermore, Quraish Shihab emphasized fiqh by explaining the prohibition on taking dowry unless proven to be fāḥisyah.